Corneal Collagen Cross-Linking Combined with an Artiflex Iris-Fixated Anterior Chamber Phakic Intraocular Lens Implantation in a Patient with Progressive Keratoconus - Hashmani, Sharif (Case Rep Ophthalmol, 2017)
We present here the case of a 24-year-old male who experienced progressive keratoconus and vision loss which adversely affected his ability to carry out everyday tasks. This landed him in the Hashmanis Hospital for consultation. He had a preoperative best corrected visual acuity of 6/12. He underwent multiple Oculus Pentacam examinations, which showed progressive keratoconus. Corneal collagen cross-linking (CXL) was performed to stabilize his cornea and, subsequently, an Artiflex anterior chamber iris-fixated phakic intraocular lens (ACIF-PIOL) was implanted to alleviate his refractive errors. The patient achieved a postoperative uncorrected visual acuity of 6/12. This report shows that CXL combined with ACIF-PIOL can be safe and effective in those with progressive keratoconus.